2014
DOI: 10.1039/c4dt01841a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of redox cooperativity and electronic structures in catalytically active Cu–Fe and Zn–Fe heterobimetallic complexes

Abstract: Complexes of the type (NHC)M-Fp (NHC = N-heterocyclic carbene, M = Cu or ZnCl, Fp = FeCp(CO)2) have been used recently as replacements for noble metal C-H functionalization catalysts and for small molecule activation studies. The promising reactivity of these systems has been linked to the use of the late metal electrophiles Cu and Zn in place of early metal electrophiles, and also to the ability of the M-Fe pairs to cooperate during catalytically relevant multielectron redox processes such as bimetallic oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…This interpretation was further supported by IR spectroscopy. The energies associated with the CO stretching modes in 1 (1910, 1840 cm −1 ) and 2 (1930, 1851 cm −1 ) are rather similar to those reported for other formally Fe 0 species, such as Cu−Fe (1914, 1849 cm −1 ) and Zn−Fe bonded complexes (1944, 1888 cm −1 ), and much lower than those for Cp(CO) 2 Fe−I (2038, 1988 cm −1 ).…”
Section: Methodssupporting
confidence: 77%
“…This interpretation was further supported by IR spectroscopy. The energies associated with the CO stretching modes in 1 (1910, 1840 cm −1 ) and 2 (1930, 1851 cm −1 ) are rather similar to those reported for other formally Fe 0 species, such as Cu−Fe (1914, 1849 cm −1 ) and Zn−Fe bonded complexes (1944, 1888 cm −1 ), and much lower than those for Cp(CO) 2 Fe−I (2038, 1988 cm −1 ).…”
Section: Methodssupporting
confidence: 77%
“…Consistent with the formally BOA process, the [Fp] fragment is oxidized during the reaction. As we have noted before, 66,68 within the [Fp] fragment the redox chemistry is dominated by the CO ligands (Table 4) and Cp ligand, and the natural charge on Fe is relatively constant (between q = −1.17 and −1.00) throughout the reaction pathway. Regarding the CH 3 Cl molecule undergoing BOA, there is essentially no change in natural charge residing on the [CH 3 ] unit.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Subsequent spectroscopic and computational analyses of the starting point and end point of this methyl iodide reaction revealed that the Cu and Fe centers participate to a surprisingly limited extent in the redox changes in the formally BOA process, whereas the redox noninnocent CO ligands within the Fp group bear a large portion of the redox changes. 68 However, no information about the pathway for alkyl halide activation was probed in that study. Before embarking on reaction kinetics analysis, we first sought to establish that the BOA process occurs by a two-electron pathway rather than by a pathway involving radical intermediates.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…[a] Entry Catalyst 1 st run After chronoamperometry [b] After chronopotentiometry [c] J280 (mA/cm 2 ) η10 (mV) J280 (mA/cm 2 ) η10 (mV) J280 (mA/cm 2 ) η10 (mV) the extraordinary WOC developed by Nature, that is the cuboidal Oxygen Evolving Complex, where a redox-inhert calcium ion has a key role in determining the activity of the manganese active sites. 85 Examples of cooperativity between Zn centers and other transition metals have been reported for some oxidation catalysts, 84,87 although further systematic studies would be necessary to draw definitive conclusions on the relationship between composition and catalytic properties of M-LDHs.…”
Section: Chronoamperometric and Chronopotentiometric Studiesmentioning
confidence: 99%